Pergeseran Model Pendampingan Penggunaan Media Digital oleh Orangtua pada Anak di Masa Pandemi COVID-19 - Syifa Syarifah Alamiyah; Ade Kusuma; Juwito Juwito; Didiek Tranggono (Universitas Mataram, 2021)
As an effort to control and handle COVID-19, the government has issued a school from home (SFH) policy. This policy has forced children to stay at home and carry out learning using digital media. This situation has an impact on increasing the use of digital media and the involvement of parents in children's learning significantly. This study explores the use of digital media in children in Surabaya during the pandemic period and how parents can assist the use of these media. This research uses qualitative methods with in-depth interview techniques. Researchers distributed questionnaires about the use of digital media to 66 parents, and nine parents stated that they were willing to become informants. The results show that in addition to a significant increase in the time to use digital media during the pandemic, the pandemic has also changed the parental assistance and supervision of children. Before the pandemic, the assistance model was carried out more with technical restrictions, in the form of time restrictions, content access, application choices, and the number of data packages (restrictive mediation). However, during a pandemic, the mentoring model was carried out with active mediation through discussions and critical thinking, active together with devices, close surveillance, and monitoring on applications and post online activities (active mediation, co-using, supervision, monitoring). One of the pandemic's positive impacts is the opening of discussion spaces between parents and children, the opportunity to use gadgets together, and opportunities for children and parents to learn digital skills.